2019
DOI: 10.1002/cam4.2187
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for acute kidney injury following autologous stem cell transplantation for multiple myeloma

Abstract: Acute kidney injury (AKI) is a common complication after allogeneic stem cell transplantation; however, its incidence and outcome in patients transplanted for multiple myeloma (MM) is unknown. We evaluated the incidence, severity, and risk factors for AKI within the first 30 days after autologous stem cell transplantation (ASCT) for MM. We prospectively followed 185 consecutive patients with MM, without chronic renal replacement therapy, who underwent ASCT; 12.5% of patients had MM‐associated amyloidosis. AKI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 38 publications
(37 reference statements)
5
19
1
Order By: Relevance
“…Complete kidney recovery has been defined as a return of serum creatinine to baseline by all studies except Parikh et al [ 14 ], who defined complete recovery as the return of serum creatinine to less than 1.2 times baseline. In accord with the notion that allogeneic HSCT is associated with an increased incidence of AKI as compared to autologous, there was a signal from two studies [ 16 , 19 ] that autologous HSCT could have better recovery rates as compared to allogeneic HSCT, but more data are required to confirm these findings. Unfortunately, kidney recovery in those cases needing RRT was dismal except for the study by Irazabal et al [ 16 ] in which half the patients recovered their kidney function after RRT.…”
Section: Discussionmentioning
confidence: 98%
“…Complete kidney recovery has been defined as a return of serum creatinine to baseline by all studies except Parikh et al [ 14 ], who defined complete recovery as the return of serum creatinine to less than 1.2 times baseline. In accord with the notion that allogeneic HSCT is associated with an increased incidence of AKI as compared to autologous, there was a signal from two studies [ 16 , 19 ] that autologous HSCT could have better recovery rates as compared to allogeneic HSCT, but more data are required to confirm these findings. Unfortunately, kidney recovery in those cases needing RRT was dismal except for the study by Irazabal et al [ 16 ] in which half the patients recovered their kidney function after RRT.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we found that patients receiving ASCT had a higher risk of AKI. This may be related to the adverse effect of calcineurin inhibitors, graft versus host disease and hepatic sinusoidal obstruction syndrome [33].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphadenopathy as well as drug-induced crystalluria (acyclovir, cotrimoxazole) can result in obstructive nephropathy. Moreover, ASCT was observed with a higher risk of AKI, involving potential mechanisms including the adverse effect of calcineurin inhibitors, graft versus host disease and hepatic sinusoidal obstruction syndrome, which can induce anemia and renal dysfunction [32].…”
Section: Discussionmentioning
confidence: 99%